Overcoming immiscibility toward bimetallic catalyst library - Yang, Chunpeng; Ko, Byung Hee; Hwang, Sooyeon; Liu, Zhenyu; Yao, Yonggang; Luc, Wesley; Cui, Mingjin; Malkani, Arnav S.; Li, Tangyuan; Wang, Xizheng; Dai, Jiaqi; Xu, Bingjun; et al. (Science advances, 2020)
A general nonequilibrium synthesis strategy is reported to address the bimetallic immiscibility challenge for catalysis. Bimetallics are emerging as important materials that often exhibit distinct chemical properties from monometallics. However, there is limited access to homogeneously alloyed bimetallics because of the thermodynamic immiscibility of the constituent elements. Overcoming the inherent immiscibility in bimetallic systems would create a bimetallic library with unique properties. Here, we present a nonequilibrium synthesis strategy to address the immiscibility challenge in bimetallics. As a proof of concept, we synthesize a broad range of homogeneously alloyed Cu-based bimetallic nanoparticles regardless of the thermodynamic immiscibility. The nonequilibrated bimetallic nanoparticles are further investigated as electrocatalysts for carbon monoxide reduction at commercially relevant current densities (>100 mA cm −2 ), in which Cu 0.9 Ni 0.1 shows the highest multicarbon product Faradaic efficiency of ~76% with a current density of ~93 mA cm −2 . The ability to overcome thermodynamic immiscibility in multimetallic synthesis offers freedom to design and synthesize new functional nanomaterials with desired chemical compositions and catalytic properties.